Gamifying sustainability : raising carbon footprint awareness through gamification : the carbon footprint movement - Nunes, Mariana Graça Paquete (2020)
Extreme human-induced environmental pressures are being felt across the globe. Scientific evidence increasingly alerts for the urgent need to induce societal engagement in climate change mitigation to achieve carbon-reduction targets. This thesis’ overreaching purpose aimed at appraising the extent to which a gamification-based system may increase carbon literacy and empower individuals to adopt lower-carbon lifestyles. Simultaneously, this study explores the hotspots where policy action should be taken to reduce the contextual barriers to more pro-environmental lifestyles. Given the multitude of factors influencing behaviors, the research herein described disaggregated national data to local levels. To attain the set objectives, a gamified-survey tool was developed, as the primary learning and data collection instrument: The Carbon Footprint Movement. Results showed carbon footprint was not a primary deliberation preceding everyday behavior and that respondents’ misconceptions regarding the environmental effects of their actions prevailed. Additional findings also reinforced contextual factors further detached intentions from behaviors, intensifying the so-called value-action gap. Notwithstanding, participants reported carbon literacy increases (23%) and pledged imminent behavioral changes, over the course of the intervention. This dissertation reinforces high-magnitude carbon emissions to be locked-in at the household level, and the potentiality of gamified interventions to unlock substantial reductions. However, it simultaneously unveils large potential savings to remain unfulfilled, suggesting active civic engagement also calls for wider structural adjustments The methodology devised might be used to guide the development of future gamified interventions.